ELM (Elaboration Likelihood Model) paradigm in snack SMEs: Experimental study - Calvin Cliff Surjadi; Teofilus Teofilus; Gladys Greselda Gosal; Auditia Setiobudi; Mohammad Fakhruddin Mudzakkir (Jurnal Ekonomi Modernisasi, 2022)
This study aims to determine whether the information quality, product variety, and packaging have a significant effect on consumer purchase intention in SMEs located in Surabaya that are engaged in the snack sector. This study uses an elaboration likelihood model theory approach to assist in analyzing the way a person processes information which will later assist in increasing purchase intention. This research uses an experimental research method, with the sample number of 270 students of Universitas Ciputra Surabaya as its participants, which are divided into 9 groups of different experimental conditions. Sampling technique uses probability sampling, and the data analysis process is done using SPSS and JASP analysis tools. The results of this research indicate that the three variables individually have a significant effect on purchase intention, but further finding shows that these three variables simultaneously do not have a significant effect on purchase intention, except for the variables representing the peripheral route, that is, product variety and packaging. Based on these findings, it is concluded that when consumers are interested in buying a product, the consumers will tend to pay attention to one thing, whether through the central route or the peripheral route.